Performance of the optical spectrum CDMA systems in FTTH access network - Mohamad Othman; Shah, N. S. M.; Noran Azizan, Cholan; Rahmat M. Talib; Samad, M. D. A .; Syed Alwee Aljunid, Syed Junid; Monir Khalil, Abdullah (Institute of Eelectrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org